The Stemmed Point Tradition of Western North America. (2nd January 2020) - Waters, Michael R.; Goebel, Ted; Graf, Kelly E.
ABSTRACT: In April 2018, the Center for the Study of the First Americans, Hakai Institute, and University of Victoria co-sponsored a five-day workshop investigating the origins of Western Stemmed technologies and their relationship with other Paleoindian and Paleolithic technocomplexes of far western North America, Beringia, and northeast Asia. This Perspective introduces the proceedings of the workshop, which are presented as a series of longer essays in this special issue of PaleoAmerica . The workshop was funded through an endowment created by Robert and Sharon Wilson at Texas A&M University to support the continued multidisciplinary investigation of the peopling of the Americas and dissemination of scientific results to the professional community and the public.